Off-Pump Coronary Artery Bypass Surgery Is Associated With Worse Arterial and Saphenous Vein Graft Patency and Less Effective Revascularization: Results From the Veterans Affairs Randomized On/Off Bypass (ROOBY) Trial - Hattler, Brack; Messenger, John C.; Shroyer, A. Laurie; Collins, Joseph F.; Haugen, Scott J.; Garcia, Joel A.; Baltz, Janet H.; Cleveland, Joseph C.; Novitzky, Dimitri; Grover, Frederick L. (Circulation (New York, N.Y.), 2012)
The Department of Veterans Affairs Randomized On/Off Bypass (ROOBY) trial compared clinical and angiographic outcomes in off-pump versus on-pump coronary artery bypass graft (CABG) surgery to ascertain the relative efficacy of the 2 techniques. From February 2002 to May 2007, the ROOBY trial randomized 2203 patients to off-pump versus on-pump CABG. Follow-up angiography was obtained in 685 off-pump (62%) and 685 on-pump (62%) patients. Angiograms were analyzed (blinded to treatment) for FitzGibbon classification (A=widely patent, B=flow limited, O=occluded) and effective revascularization. Effective revascularization was defined as follows: All 3 major coronary territories with significant disease were revascularized by a FitzGibbon A-quality graft to the major diseased artery, and there were no new postanastomotic lesions. Off-pump CABG resulted in lower FitzGibbon A patency rates than on-pump CABG for arterial conduits (85.8% versus 91.4%; P=0.003) and saphenous vein grafts (72.7% versus 80.4%; P<0.001). Fewer off-pump patients were effectively revascularized (50.1% versus 63.9% on-pump; P<0.001). Within each major coronary territory, effective revascularization was worse off pump than on pump (all P≤0.001). The 1-year adverse cardiac event rate was 16.4% in patients with ineffective revascularization versus 5.9% in patients with effective revascularization (P<0.001). Off-pump CABG resulted in significantly lower FitzGibbon A patency for arterial and saphenous vein graft conduits and less effective revascularization than on-pump CABG. At 1 year, patients with less effective revascularization had higher adverse event rates. URL: http://www.clinicaltrials.gov. Unique identifier: NCT00032630.